Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.11606/s1518-8787.2020054002108
|View full text |Cite
|
Sign up to set email alerts
|

Coinfecção TB-HIV

Abstract: OBJETIVO: Descrever a distribuição espacial e temporal da coinfecção TB-HIV, assim como o perfil das características da população coinfectada no município de São Paulo. MÉTODOS: E studo e cológico e d e s érie t emporal c om d ados d o S istema d e C ontrole d e Pacientes com Tuberculose (TBWeb), incluindo todos os casos novos de tuberculose coinfectados pelo HIV residentes no município no período de 2007 a 2015. Tendências temporais do agravo foram analisadas por regressão de Prais-Winsten. Os casos foram geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
15

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 35 publications
(120 reference statements)
2
15
0
15
Order By: Relevance
“…Some studies conducted in Brazil [ 50 , 57 , 58 ] also showed that strong spatial clustering of TB and TB/HIV observed in urban areas and semi-urban areas with a high population density and market places.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies conducted in Brazil [ 50 , 57 , 58 ] also showed that strong spatial clustering of TB and TB/HIV observed in urban areas and semi-urban areas with a high population density and market places.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from similar studies conducted in Ethiopia [ 13 , 14 ] revealed educational status, wealth index, migrations, drug dependency, WHO clinical stage, and baseline CD4 count as significant predictors of this TB/HIV co-infection. Additionally, the results of other related studies conducted in several countries identified poverty, poor healthcare, drug, and alcohol misuse, and mental disorders as the main determinant factors for the spatial variation of TB/HIV co-infection [ 14 , 17 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with the Human Immunodeficiency Virus (HIV) is a significant challenge for tuberculosis (TB) control, with increasing mortality rates worldwide [ 1 ]. Until the coronavirus (COVID-19) pandemic, TB was the leading cause of death from a single infectious agent [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunological impairment caused by HIV/AIDS increases the multiplication of M. tuberculosis and the degree of illness with TB [ 1 ]. The joint treatment of TB and HIV/AIDS (coinfected) reduces mortality, TB recurrence, and the transmission of both diseases in the community [ 5 ].…”
Section: Introductionmentioning
confidence: 99%